Synovial Fluid Biomarkers in Knee Osteoarthritis: A Systematic Review and Quantitative Evaluation Using BIPEDs Criteria. (December 2021) - Boffa, Angelo; Merli, Giulia; Andriolo, Luca; Lattermann, Christian; Salzmann, Gian M.; Filardo, Giuseppe
Objective: The aim of this systematic review was to analyze the evidence about the efficacy of the several synovial fluid (SF) biomarkers proposed for knee osteoarthritis (OA), categorizing them by both molecular characteristics and clinical use according to the BIPEDs criteria, to provide a comprehensive and structured overview of the current literature. Design: A systematic review was performed in May 2020 on PubMed, Cochrane Library, and Embase databases about SF biomarkers in patients with knee OA. The search was limited to articles in the last 20 years on human studies, involving patients with knee OA, reporting SF biomarkers. The evidence for each selected SF biomarker was quantified according to the 6 categories of BIPEDs classification. Results: A total of 159 articles were included in the qualitative data synthesis and 201 different SF biomarkers were identified. Among these, several were investigated multiple times in different articles, for a total of 373 analyses. The studies included 13, 557 patients with knee OA. The most promising SF biomarkers were C4S, IL-6, IL-8, Leptin, MMP-1/3, TIMP-1, TNF-α, and VEGF. The "burden of disease" and "diagnostic" categories were the most represented with 132 and 106 different biomarkers, respectively. Conclusions: The systematic review identified numerous SF biomarkers. However, despite the high number of studies on the plethora of identified molecules, the evidence about the efficacy of each biomarker is supported by limited and often conflicting findings. Further research efforts are needed to improve the understanding of SF biomarkers for a better management of patients with knee OA.